Scaled CO Electroreduction to Alcohols - Panagiotis Papangelakis; Colin P. O’Brien; Ali Shayesteh Zeraati; Shijie Liu; Alexander Paik; Vivian Nelson; Sungjin Park; Yurou Celine Xiao; Roham Dorakhan; Puhua Sun; Jinhong Wu; Christine M. Gabardo; et al. (Nature Communications)
Abstract Electrocatalysis offers a promising route to convert CO2 into alcohols, which is most efficient in a two-step cascade reaction with CO2-to-CO followed by CO-to-alcohol. However, current alcohol-producing CO2/CO electrolyzers suffer from low selectivity or alcohol crossover, resulting in alcohol concentrations of less than 1%, which are further diluted in downstream cold-traps. As a result, electrocatalytic alcohol production has yet to be scaled beyond the lab (1-10 cm2). Here, we reverse the electroosmotic drag of water using a cation exchange membrane assembly, enabling the recovery of over 85% of alcohol products at a concentration of 6 wt.%. We develop a multi-step condenser strategy to separate the produced alcohols from the effluent gas stream without dilution. Scaling up this approach to an 800 cm2 cell resulted in an output of 200 mL alcohol/day.